The importance of virtual environments for the teaching and learning of foreign languages - Guzmán Hernández, Josué David; Navarro Melgar, Sergio Julio; Argueta Ramos, Vicente Paul (2024)
The investigation covered an analysis and summary of the specialization about virtual environments coming from the foreign language department; this with the purpose of expressing what it was learned and practice during the program and at the same time to be a good test for future groups that will go into the same process. This new way of teaching can bring a great experience to teacher and future teachers, to offer more learning options and to be a more complete version of a teacher so the needs of the students can be covered in a better timing with more tools, and options that can make the learning experience better, and more productive no matter time or place. As well, a benefit of having more tools, make students more productive and more convinced on what they have for learning, make classes more interactive and at the same time more commitment built due to the variety of options for better learning. Key words: Virtual ; Teaching ; Learning ; Practice ; Experience ; Tools ; Languages.